Epistemic Logic Based on Dolev-Yao Model - Benevides, Mario R. F.; Fernandez, Luiz C. F.; de Oliveira, Anna C. C. M. (Anais do Encontro de Teoria da Computação (ETC), 2017)
In this work, we extend multi-agent epistemic logic for reasoning about properties in protocols. It is based on Dolev-Yao model and uses structured propositions, a new technique to deal with messages, keys and properties in security protocols in an uniform manner, keeping the logic propositional. In order to illustrate the applicability of this new logic, an example is presented.